Exploration of the role of the upper brainstem in motor control. - Nandi, D; Stein, J; Aziz, T (2002)
The rostral areas of the brainstem have been extensively studied in higher mammals and to a lesser extent in humans in the last two decades, looking for anatomical, electrophysiological and neurochemical evidence of involvement in the initiation and control of voluntary movement. This has come with the realisation that the axial symptoms of advanced Parkinson's disease (PD), like akinesia, postural impairment and gait freezing, are relatively less responsive to current medical and surgical treatments directed primarily at the basal ganglia and thalamus. The pedunculopontine nucleus (PPN) is one such area of interest. We have found that lesioning and electrical stimulation at high frequencies of the PPN region in the normal behaving primate induces akinesia, and low frequency stimulation can induce tremor. Micro-injections of gamma-aminobutyric acid (GABA) receptor A agonist, muscimol, into the PPN decreases activity. In the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) treated Parkinsonian primate model, bicuculline, a GABA(A) antagonist, can alleviate akinesia when infused into the PPN region. This may suggest new targets for treating the intractable akinetic symptoms of advanced PD.